BUILDING BRAND EVANGELISM THROUGH BRAND EXPERIENCE AND BRAND INNOVATION AMONG MILLENNIAL CONSUMERS IN THE SMARTPHONE BUSINESS - Saewanee, Cholthida; Kedtongma, Alisa; Chueabunkoet Noth, Arirat (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This study aims to: (1) examine the effect of brand experience on brand innovation and brand evangelism, (2) investigate the impact of brand innovation on brand evangelism, (3) explore the mediating role of brand innovation in the relationship between brand experience and brand evangelism, and (4) summarize the relationship between brand experience and brand innovation in fostering brand evangelism among millennial consumers in the smartphone industry. The research employed a structured online questionnaire as the primary data collection instrument. The sample consisted of 446 millennial consumers who had used or experienced using a smartphone within the six-month period from May to October 2024. A non-probability sampling method, specifically snowball sampling, was used to recruit participants. Data were analyzed using descriptive statistics, including percentage, mean, and standard deviation, through statistical software. The quality of the measurement model was assessed using confirmatory factor analysis (CFA), and the hypotheses were tested via structural equation modeling (SEM). In addition, the indirect effects and mediation analysis were conducted using the bootstrapping technique. The results revealed that: (1) brand experience has a positive influence on both brand innovation and brand evangelism; (2) brand innovation positively affects brand evangelism; (3) brand innovation partially mediates the relationship between brand experience and brand evangelism; and (4) brand evangelism can be cultivated either directly through brand experience and brand innovation, or it can begin with brand experience and subsequently be developed through brand innovation. This study contributes to the academic literature on brand management by offering a consumer-based perspective and provides practical implications for enhancing competitive advantage through strategic brand experience and innovation.